The Viana footbridge: construction and dynamic monitoring - R. Barbosa (2013)
A new moveable footbridge was recently built at the entrance of Marina Atlantico in the city of Viana do Castelo, Portugal. This paper presents a brief description of the global solution, with a special focus on the characterisation of the construction methods adopted. Particular consideration is given to the construction of the pivot pylon and the steel structure, showing how all the bridge components work together to ensure a safe working relationship with the marina, the river and users of the continuous bicycling and pedestrian pathway running across the closed bridge. The mechanical, hydraulic, electrical and navigational light systems play fundamental roles, especially during bridge opening and closing operations. Moreover, as this light footbridge is susceptible to vibrations due to human traffic, the paper also describes the dynamic tests performed during and after construction, including two ambient vibration tests, the measurement of cable-stay forces, and tests with groups of pedestrians used to evaluate induced vibration levels along with the monitoring of bridge accelerations over 4 months of use.